Social and Emotional Learning and Internalizing Problems among Adolescents: The Mediating Role of Resilience - Aurora Adina Colomeischi; Andreea Ursu; Ionela Bogdan; Alina Ionescu-Corbu; Romina Bondor; Elisabetta Conte (MDPI AG, 2022)
(1) Background: The high rates of mental disorders in adolescence presented in the literature often exclude internalizing problems. Although there is extensive data on the effectiveness of SEL skills in improving resilience, few studies included evidence in their reports on the relationship between SEL skills and internalizing problems. The present study aims to deepen the understanding of the relationship between SEL, resilience, and internalizing problems, by investigating the mediating effect of resilience between SEL components and internalizing problems. (2) Methods: Adolescents (N = 968 adolescents, aged between 11 and 18 years old; M = 13.30; SD = 1.92) from 30 schools from the NE region of Romania were invited to fill out questionnaires on social and emotional learning, internalizing problems, and resilience. (3) Results: The results show that resilience mediates the link between self-awareness and internalizing problems, between self-management and internalizing problems, between relationship skills and internalizing problems, and between responsible decision-making and internalizing problems. (4) Conclusions: These findings revealed the need for social and emotional learning interventions that include resilience-oriented approaches in order to decrease internalizing problems in adolescents. Moreover, we suggest that more culturally appropriate interventions are required to better investigate the interaction between SEL components, resilience, and internalizing problems.